Encapsulation, Visualization and Expression of Genes with Biomimetically Mineralized Zeolitic Imidazolate Framework‐8 (ZIF‐8). Issue 36 (1st July 2019) - Poddar, Arpita; Conesa, José J.; Liang, Kang; Dhakal, Sudip; Reineck, Philipp; Bryant, Gary; Pereiro, Eva; Ricco, Raffaele; Amenitsch, Heinz; Doonan, Christian; Mulet, Xavier; Doherty, Cara M.; et al.
Abstract: Recent work in biomolecule‐metal–organic framework (MOF) composites has proven to be an effective strategy for the protection of proteins. However, for other biomacromolecules such as nucleic acids, the encapsulation into nano MOFs and the related characterizations are in their infancy. Herein, encapsulation of a complete gene‐set in zeolitic imidazolate framework‐8 (ZIF‐8) MOFs and cellular expression of the gene delivered by the nano MOF composites are reported. Using a green fluorescent protein (GFP) plasmid (plGFP) as a proof‐of‐concept genetic macromolecule, successful transfection of mammalian cancer cells with plGFP for up to 4 days is shown. Cell transfection assays and soft X‐ray cryo‐tomography (cryo‐SXT) demonstrate the feasibility of DNA@MOF biocomposites as intracellular gene delivery vehicles. Expression occurs over relatively prolonged time points where the cargo nucleic acid is released gradually in order to maintain sustained expression. Abstract : Metal–organic frameworks like zeolitic imidazolate framework‐8 (ZIF‐8) can successfully encapsulate intact genes and not just synthetic, functionally‐inert DNA strands. The encapsulated genes retain their functional integrity by showing protein expression; allowing for the use of ZIF‐8 as vehicles of intracellular transfection and gene delivery to cause gradual expression of foreign DNA inside human epithelial prostate cancer cells.